Hadith #801 - Sahih Muslim - Mansur bin 'Abdur Rahman bin Talha منصور بن عبد الرحمن بن طلحة الحجبي (Sahih Muslim)
” Then he may choose any supplication which pleases him or which he likes.”
Grade: Sahih